THE INFLUENCE OF DISCIPLINE, JOB SATISFACTION AND MOTIVATION ON WORK PRODUCTIVITY AT THE CENTER FOR STATISTICS (BPS) OF ACEH TENGGARA DISTRICT - Muridha Hasan (SEAN Institute, 2023)
This study aims to see the effect of discipline, job satisfaction and motivation on work productivity at the Central Bureau of Statistics in Southeast Aceh District. This data uses primary data obtained by directly interviewing respondents using a questionnaire. To find out the effect of Discipline, job satisfaction and motivation on work productivity at the Central Statistics Agency for Southeast Aceh District, a multiple linear regression method was used using processing tools in this study in the form of SPSS version 16. In the multiple linear regression stages, classical assumption tests were first performed. To determine the effect of Discipline, job satisfaction and motivation both partially and simultaneously, t-test and F-test were carried out. The results found partially that both job satisfaction and motivation had a significant effect on work productivity, while the results of the joint tests showed that Discipline, job satisfaction work and motivation have a significant effect on work productivity in the Central Bureau of Statistics in Southeast Aceh District.